Development of a GIS-Based Underground Utility Mapping System for Facilities Management at UTHM Pagoh Campus - Mazarina Sabirah; Abd Sukor Sarif (Progress in Engineering Application and Technology, 2026)
Underground utilities such as water, electricity, drainage, and telecom cables are critical infrastructure for a campus. The current utility maps are outdated and scattered are found in many sources. The data on the UTHM Pagoh campus’s infrastructure had been stored in CAD software and scanned images, which was a slow process. This study aimed to create a GIS-based underground utility map and database for UTHM Pagoh Campus and to demonstrate the application of the GIS-based system in supporting maintenance decision-making. This study focus on create a GIS mapping system for water pipelines, sewerage networks, and drainage to improve the management of utility information. The process of digitizing and georeferencing of the data on the existing underground utilities on campus was done using QGIS software. The results showed that the GIS successfully integrated multiple data on the utility on a single geographical platform. The study results confirm the usability of the GIS system as a decision-support tool for the detection of utilities prior to maintenance activities. The underground utility mapping GIS system has increased the level of facilities management efficiency at UTHM Pagoh campus.